The tea girl of Hummingbird Lane : a novel - See, Lisa (New York : Scribner, 2017)
"A thrilling new novel from #1 New York Times bestselling author Lisa See explores the lives of a Chinese mother and her daughter who has been adopted by an American couple. Li-yan and her family align their lives around the seasons and the farming of tea. There is ritual and routine, and it has been ever thus for generations. Then one day a jeep appears at the village gate--the first automobile any of them have seen--and a stranger arrives. In this remote Yunnan village, the stranger finds the rare tea he has been seeking and a reticent Akha people. In her biggest seller, Snow Flower and the Secret Fan, See introduced the Yao people to her readers. Here she shares the customs of another Chinese ethnic minority, the Akha, whose world will soon change. Li-yan, one of the few educated girls on her mountain, translates for the stranger and is among the first to reject the rules that have shaped her existence. When she has a baby outside of wedlock, rather than stand by tradition, she wraps her daughter in a blanket, with a tea cake hidden in her swaddling, and abandons her in the nearest city. After mother and daughter have gone their separate ways, Li-yan slowly emerges from the security and insularity of her village to encounter modern life while Haley grows up a privileged and well-loved California girl. Despite Haley's happy home life, she wonders about her origins; and Li-yan longs for her lost daughter. They both search for and find answers in the tea that has shaped their family's destiny for generations. A powerful story about a family, separated by circumstances, culture, and distance, Tea Girl of Hummingbird Lane paints an unforgettable portrait of a little known region and its people and celebrates the bond that connects mothers and daughters"--
"A thrilling new novel from #1 New York Times bestselling author Lisa See explores the lives of a Chinese mother and her daughter who has been adopted by an American couple"--
Keywords: Adopted children -- Fiction; Chinese-American teenagers -- California -- Fiction; Identity (Psychology) -- Fiction; Mothers and daughters -- Ficiton; Akha (Southeast Asian people) -- China -- Fiction; Group identity -- China -- Fiction; FICTION / Literary; FICTION / Sagas; Psychological fiction; Domestic fiction